Code-Based Signature Schemes For Online Voting System Based On The Blockchain Technology - Lee, Feng Wei (2022)
Post-quantum cryptography has been one of the focuses of researchers since the initiation of quantum algorithms. One of the main approaches of postquantum cryptography is code-based cryptography. It is constructed using coding theory-based hardness assumptions. Since code-based hardness assumptions are the foundation of code-based cryptography, thus, we first investigate various code-based hard problems. We start by studying the relationship between various code-based hard problems and code-based cryptographic primitives in this research. Besides, we also provide a thorough analysis of the relationship between these hard problems by reducing them to some well-known mathematical hard problems. After understanding the codebased hard problems, we construct a code-based signature scheme and a codebased ring signature scheme. Both of the constructed signature scheme and ring signature scheme are based on Classic McEliece KEM that acts as the finalist of NIST's post-quantum standardization project. We then move on to the security and efficiency analysis of our constructed signature schemes. Both schemes are existentially unforgeable under chosen message attacks. Besides, the ring signature scheme possesses unconditional signer ambiguity and is unforgeable against fixed ring attacks. After the construction of these cryptographic primitives, we look into the possibility of implementations of these signature schemes for the online voting system based on the blockchain technology. This investigation is motivated by the conventional blockchain architecture which is not quantumresistant. Thus, the investigation of the post-quantum blockchain is a concern. As a result, we construct a ring signature scheme with the anonymity property. This property plays an important role when it comes to blockchain applications. It helps to hide the identity of the users inside the blockchain. Throughout the research, we notice that a code-based key exchange protocol that is able to produce a common error pattern as a common key is also very important for code-based cryptographic primitives. Thus, we introduce a new code-based key exchange protocol that is constructed using the Permuted Goppa Syndrome Decoding Problem. Last but not least, comprehensive security of the constructed protocol is provided and the protocol is secured under the CK model.